EVALUATION OF DIFFERENT SOLID AND LIQUID MEDIA FOR THE GROWTH AND SCLEROTIAL FORMATION OF MACROPHOMINA PHASEOLINA (TASSI) GOID IN VITRO - D. H. TANDEL,; A. N. SABALPARA,; R. C. PATEL, (The Bioscan, 2012)
Eight different media including synthetic and semi synthetic in solid and liquid state were tested for their suitability to the growth and sclerotial formation of the fungus, Macrophomina phaseolina. The growth of M. phaseolina was significantly more on potato dextrose agar (89.67mm) as compared to the rest but was at par with potato carrot sucrose agar (86.67mm). The sclerotial formation of M. phaseolina was high on potato dextrose agar, potato carrot sucrose agar and Richard’s agar. Among the various liquid media tested, significantly higher dry mycelial weight was yielded in Richards’ solution (776.25mg) as compared to the rest of the liquid media but was at par with Czapek’s Dox solution (758.68mg). The sclerotial formation was found high level on Richards’ solution, Czapek’s Dox solution, potato dextrose broth and potato carrot sucrose broth.